Potencial alelopático de diferentes espécies de plantas sobre a qualidade fisiológica de sementes de arroz e aquênios de alface e crescimento de plântulas de arroz e alface - Comiotto, Andressa (2006)
The objective of this work was to analyze and to describe the influence of aqueous extracts of Echinochloa cruzgalli L., Cyperus sp. and Sagittaria montevidensis about the physiological quality of the seeds and growth of seedlings of rice Atalanta . The extracts were acquired from species collected on rice planting areas and in the campus of UFPel. The essays were accomplished at laboratory with different concentrations (zero, 25, 50, 75 and 100%) of aqueous extracts of leaves (vegetal fresh material, w/v). The rice Atalanta seeds were put to soak for 60 minutes in the different aqueous extracts and concentrations, and then conducted to germination, first counting of germination, germination speed rate, aerial part and root length, and electric conductivity tests. It could be observed that the extracts did not have influence about the germination and first germination counting, but there was influence in the germination speed rate and in the leaching of reserve compounds. It could be concluded the occurrence of negative differential plant toxicity. The objective of this work was to analyze and to describe the influence of aqueous extracts of Schinus terebinthifolius Raadi over achenes and the growth of seedlings of lettuce Branca de Boston . The extract was acquired from species collected in the campus of UFPel. The essays were accomplished at laboratory, and the concentrations were (zero, 50 and 100%) of aqueous extracts of leaves (vegetal fresh material, w/v). Achenes of lettuce Branca de Boston were put to soak for 60 minutes in the different extracts concentrations and than conducted to the tests: germination, first counting of germination, germination speed rate, length of the seedlings, fresh and dry mass and electrical conductivity. It could be concluded that the extract exerts negative fitotoxic effect over the achenes and over the growth of lettuce seedlings, in both concentrations used, being more expressive according to the increase of the extract concentration.